2020
DOI: 10.1186/s12199-020-00904-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors involved in SARS-CoV-2 transmission: effect and role of indoor environmental quality in the strategy for COVID-19 infection control

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a new zoonotic agent that emerged in December 2019, causes coronavirus disease 2019 (COVID-19). This infection can be spread by asymptomatic, presymptomatic, and symptomatic carriers. SARS-CoV-2 spreads primarily via respiratory droplets during close person-to-person contact in a closed space, especially a building. This article summarizes the environmental factors involved in SARS-CoV-2 transmission, including a strategy to prevent SARS-CoV-2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
157
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 89 publications
2
157
0
3
Order By: Relevance
“…Some models under this family, add compartments, like the E compartment, under the SEIR model, that corresponds to Exposed individuals that do not spread the infection, since they have a latent asymptomatic infection but are not infectious, which is not the case for SARS-CoV-2 given that asymptomatic patients can also spread the disease ( Figure 2a ), and also, can consider the rate of becoming susceptible again after infection, as would be important in the case of reinfection ( Figure 2a ), a plausible but uncertain phenomenon in the case of SARS-CoV-2, 17 and the rate of infection from different human to human sources, like contaminated surfaces (sparking rate, Figure 2a ), as has been documented for SARS-CoV-2 and other viruses. 18
Figure 2. Schematic diagram of between-host (a) and intra-host virus (b) dynamics.
…”
Section: Using Phylodynamics For Infectious Disease Modeling and Undementioning
confidence: 99%
“…Some models under this family, add compartments, like the E compartment, under the SEIR model, that corresponds to Exposed individuals that do not spread the infection, since they have a latent asymptomatic infection but are not infectious, which is not the case for SARS-CoV-2 given that asymptomatic patients can also spread the disease ( Figure 2a ), and also, can consider the rate of becoming susceptible again after infection, as would be important in the case of reinfection ( Figure 2a ), a plausible but uncertain phenomenon in the case of SARS-CoV-2, 17 and the rate of infection from different human to human sources, like contaminated surfaces (sparking rate, Figure 2a ), as has been documented for SARS-CoV-2 and other viruses. 18
Figure 2. Schematic diagram of between-host (a) and intra-host virus (b) dynamics.
…”
Section: Using Phylodynamics For Infectious Disease Modeling and Undementioning
confidence: 99%
“…People may also become infected through physical contact of virus-contaminated objects such as solid waste ( Al Huraimel et al, 2020 , Ben-Shmuel et al, 2020 , Suman et al, 2020 ). Aerosol transmission in a relatively closed environment ( Azuma et al, 2020 , Zhao et al, 2020 , Tung et al, 2021 ), such as hospital locals have been confirmed ( Shi et al, 2020 ). In addition, environmental pollution caused by feces and urine aerosols ( Heller et al, 2020 ) or physical contact in toilets ( Hoseinzadeh et al, 2020 , Mehraeen et al, 2020 , Pamplona et al, 2020 ) could pose a major transmission risk.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the high infectivity and mutability of COVID-19, the environmental transmission routes of SARS-CoV-2 are a subject of urgent research. Some studies identify the main routes of transmission as respiratory droplets ( Azuma et al, 2020 , Marin-Garcia et al, 2021 ) and close contact ( Martinez-Fierro et al, 2021 ). People may also become infected through physical contact of virus-contaminated objects such as solid waste ( Al Huraimel et al, 2020 , Ben-Shmuel et al, 2020 , Suman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a public health emergency of international concern [1] . The most common symptoms of patients with COVID-19 are fever, cough, shortness of breath, and myalgia/fatigue [1] . Anosmia (loss of smell) and dysgeusia (altered sensation of taste) have been reported in 33–80% of patients with COVID-19 [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Anosmia (loss of smell) and dysgeusia (altered sensation of taste) have been reported in 33–80% of patients with COVID-19 [2] . SARS-CoV-2 is mainly transmitted human-to-human through close contact, respiratory droplets, fomites, and contaminated surfaces [1] . Importantly, a chronic post-viral syndrome characterized by chronic fatigue, variable nonspecific myalgia, depression and sleep disturbances has previously been reported following SARS coronavirus infection, which emerged from South East Asia in early 2003 [3] .…”
Section: Introductionmentioning
confidence: 99%